Metallogeny and petrogenesis of lamprophyres in the mid-European Variscides : post-collisional magmatism and its relationship to late-Variscan ore forming processes in the Erzgebirge (Bohemian Massif) - Seifert, Thomas (Millpress/IOS Press ; Distributor in the USA and Canada, IOS Press, 2008)
Presents a model important for the exploration for Sn, W, Mo, Ag, Cu, Zn, Pb, In, and U mineralization in the Bohemian Massif and comparable ore deposit provinces worldwide.